Apocalyptic fiction - Tate, Andrew 1971 (London Bloomsbury Academic, 2017)
Visions of post-apocalyptic worlds have proved to be irresistible for many 21st-century writers, from literary novelists to fantasy and young adult writers. Exploring a wide range of texts, from the works of Margaret Atwood, Cormac McCarthy and David Mitchell to young adult novels such as Suzanne Collins's The Hunger Games series, this is the first critical introduction to contemporary apocalyptic fiction. Exploring the cultural and political contexts of these writings and their echoes in popular media, Apocalyptic Fiction also examines how contemporary apocalyptic texts looks back to earlier writings by the likes of Mary Shelley, H.G. Wells and J.G. Ballard. Apocalyptic Fiction includes an annotated guide to secondary readings, making this an essential guide for students of contemporary fiction at all levels.
1. Introduction: Dreams of the 'ruined' future -- 2. 'God rains over everything': Two floods -- 3. 'Sudden departure': Rapture writing -- 4. 'In the beginning, there was chaos': Atwood, apocalypse, art -- 5. Empty roads: Walking after catastrophe -- 6. Keep watching: Spectacle, rebellion and apocalyptic rites of passage -- 7. Conclusion: 'Survival is insufficient.'
Includes bibliographical references (pages 139-171) and index.
Keywords: Apocalypse in literature; Fiction -- History and criticism